Manajemen Peningkatan Lulusan Siswa di Sekolah Menegah Pertama Negeri 1 Sangatta Utara - Mutasyarifin, Aham (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
Abstract This research aims to analyze the planning, organization, implementation and evaluation in the management of student graduates at SMPN 1 Sangatta Utara, which successfully graduated all its students. The research method used is descriptive qualitative with a descriptive approach. Data was obtained through interviews, observation, and documentation with the main informants, principals, deputy principals for curriculum, student affairs, and teachers. The validity of the data was tested through source triangulation, and analysis was carried out descriptively. The research results show that management functions are implemented effectively: 1) Planning is carried out through coordination meetings to prepare integrated programs without disturbing the main schedule. 2) Organization is carried out by the school principal giving authority to the deputy head of curriculum to appoint the person in charge of the program. 3) Implementation involves technology-based learning, increasing academic competence, and routine religious formation. (4) Evaluations are carried out periodically to measure program effectiveness and identify obstacles. This research concludes that the application of management functions supports the success of improving the quality of graduates. Recommendations are aimed at strengthening collaboration between related parties for program sustainability